QUESTION WORDS IN ENGLISH AND NORTH ACEH DIALECT OF ACEHNESE - Feenna Nuzula; Zainuddin Zainuddin; Ade Aini Nuran (State University of Medan, 2019)
This study dealt with Question Word in English and North Aceh Dialect of Acehnese. The objectives of the study were to investigate the similarities, differences, and implication of question words in English and Acehnese by using Paul’s theory. This study was conducted by using descriptive library research. The data of this study were taken from some books of English and Acehnese grammatical structure. For collecting data, this study used the method of contrastive analysis. The findings showed that there were five similarities and seven differences based on form and function. Question word in English and Acehnese were partly-correspondences in terms of form. There were the question word in both languages can be placed at the beginning of question, while Acehnese question word can be placed in the middle of question after added a based word /tu-/ that can produce a new question word. In term of function, Question word in English and Acehnese were partly-correspondences because both languages were asking about informations, while in English there were two question words that can change the basic function after added the word “about”.Keywords: Question Word, English, North Aceh Dialect, Acehnese.